ANALISI KUALITAS SALA KEJU - Yulianto, Deri; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The purpose of this research was to analyse the effect of the use of chesse for 0 gr, 40 gr, 55 gr, 70 gr, and 85 gr for the shape quality color, smell, texture and taste of Sala Keju produced. This research is pure experiment whit compelete random design method. Variabel X (the use of chesse) and variabel Y (quality of Sala Keju) the data that researcher use is primary data which obtained directly from 30 trained. Data analyse with ANAVA, if different will be continiou with Duncan test. The result of this reseach showed there was a different in the effect of the use of cheese with color, smell quality, savory test and cheese flavour. Whereas for the quality of round shape, similar shape and there is no different effect for the texture wich the best result of Sala Keju was use cheese in 40 gr (X1).Keywords: Sala, cheese, Quality